Vertical distribution of the soil phosphorus from the triple superphosphate (Research, Society and Development, 2020)
The objective of the present work was to estimate the rate of vertical movement of triple superphosphate to soils with sandy texture, medium texture and clay texture. The work was conducted in pots, irrigated daily with distilled water, of which 10 pots were filled with soil of sandy texture (Quartzarenic Neosol), 10 with medium texture () and 10 with clay texture (Red Argissolo), in which, for each group of ten vessels, 5 were fertilized with triple superphosphate and 5 were used for control (without fertilizer deposition). These vessels were mounted with 150 mm pvc pipes, cut to a height of 2 cm each ring, each vessel was composed of 10 rings glued by adhesive tape. For the analyzes, 300 samples were taken from the center of each ring, dried, piped and subjected to P analysis by the Melich-1 method. The soil that had the best response to the fertilization was the clay one, while the sandy and the medium texture showed little mobility of the phosphorus and, consequently, its greater retention in the more superficial layers.